Conceptual layout of a helium cooling system for the Einstein Telescope. Issue 1 (1st May 2022) - Busch, L; Grohmann, S
Abstract: The Einstein Telescope (ET) is a 3 rd generation gravitational-wave detector planned in triangular shape with 10 km arm lengths in an underground installation at a depth of 200m to 300 m. While 2 nd generation detectors and the ET high-frequency interferometer are operated at room-temperature, the ET low-frequency (LF) interferometer shall be operated at cryogenic mirror temperatures of 10K to 20K in order to reduce the thermal noise. Considering thermal dissipation limits in the heat extraction path from the mirror to the heat sink, He-II provides ultra-low-noise cooling to allow for an interferometer sensitivity at levels below 1 × 10 −20 m/ Hz in the detection band. In order to limit particle adsorption on the cold mirror surface, the total pressure in the cryostat must be reduced to p ≤ 1 × 10 −10 mbar, i.e. partial pressures of water and heavier components pi ≤ 1 × 10 −14 mbar, respectively, using a cryopump/shield around the mirror that is cooled with supercritical helium to T ≈ 5K. We present the conceptual layout of a helium cooling system that can provide cooling power for several ET-LF cryostats and their corresponding cryotraps, including mirror cooling at 2K as well as thermal shielding at 5K and at 50K to 80K. A process flow diagram focuses on the cooling system's key components with their locations and their interconnections. On the diagram's basis, we explain the cooldown process and steady-state operation, ranging from outer shield and cryotrap cooling to the formation of He-II in the mirror heat extraction path.